Portable and power-free serodiagnosis of Chagas disease using magnetic levitating microbeads. Issue 18 (20th August 2018) - Castro, Beatriz; Sala de Medeiros, Marina; Sadri, Behnam; Martinez, Ramses V.
Abstract : Magnetic levitating microbeads enable the point-of-care detection of Chagas antibodies in blood solutions using a portable magnetic stage requiring no electricity. Abstract : This work describes the detection of anti- T. cruzi antibodies in whole blood solutions using magnetic levitating microbeads (MLμBs). This simple diagnostic method can be easily performed by minimally trained personnel using an inexpensive and portable magnetic stage that requires no electricity. A multiphase test tube containing the MLμBs facilitates the sequential incubation, filtering, and reading of the immunoassays. The diagnostic method starts by adding a blood sample to the top phase of the test tube where the anti- T. cruzi antibodies present in the blood attach to the T. cruzi antigens on the surface of the MLμBs. Shaking the test tube after incubation mixes the top layer with a paramagnetic medium loaded with SiO2 microcrystals. The attachment of SiO2 microcrystals to those MLμBs bound to T. cruzi antibodies decreases their levitation height once the tube is placed between two antialigned permanent magnets. Measuring the levitation height of MLμBs enables the accurate detection and quantification of anti- T. cruzi antibodies in the blood across the clinically relevant range, with a detection limit of 5 μg mL −1 . The small size of the test tubes facilitates the simultaneous analysis of over 50 different samples. MLμBs act as partial collimators for non-polarized light, facilitating their visual identification by the naked eye or by projecting incident light on a thin paper screen. A machine-vision algorithm was created to automatically interpret the results of the MLμB tests from a digital image, resulting in a rapid, accurate, and user-friendly assay for Chagas disease that can be used in resource-limited settings.